Maimonides's Skeptical Critique of a Divine Intellect, or the Curious Case of Guide I.68. - Stern, Josef (Journal of the History of Philosophy, 2026)
The philosophers' dictum in Maimonides's Guide of the Perplexed I.68 has been classically read as Maimonides's own opinion that God's intellect in act is identical to the intellecting subject in act and intellectum in act, no different from a human intellect in act. This reading of the chapter generates multiple puzzles and contradicts Maimonides's views elsewhere. I argue instead that the chapter is Maimonides's skeptical critique of the philosophers' (not his own) conception of God's intellect, that careful analysis shows that Maimonides presents four differences between the human and divine intellects, and that the divine intellect, unlike the human, is entirely unknowable.